Menerapkan Makna Sakai Sambayan sebagai Nilai Kearifan Lokal Masyarakat Lampung dalam Pembelajaran Bahasa Indonesia: Perspektif Pendidikan Islam - Palyanti, Mega; Dessy Kemala Sari; M.Tegar Alvian Saputra; Ani Musriani (Bulletin of Community Engagement, 2024)
This research aims to explain how the values of Islamic education are integrated into the Nima culture of the Pepadun community in Lampung. The form of Nemui Nyimah culture in the Tiyuh Panaragan community can be seen in hospitality activities, such as procedures or manners for visiting and receiving guests. The data analysis techniques researchers use are data reduction, data display and conclusion drawing/validation. Data was collected through participant observation, in-depth interviews, and note-taking. The findings show that "Nemui Nyimah" is not just a form of politeness but is also a social mechanism that strengthens community ties and upholds local cultural values. This tradition involves various stages, from preparation and reception to a meal accompanied by certain symbols and rituals. These findings provide an overview of how the practice of "Nemui Nyimah" plays a role in the daily lives of the Lampung people and its contribution to the preservation of traditional culture in the midst of the modernization process. The results of this research show that: The implementation of the Nemui Nyimah culture in the Tiyuh Panaragan community can be seen in reception activities, such as the layout. manners in visiting and receiving guests in the Tiyuh Panaragan community. Based on existing findings, Nemui Nyimah is an explicit culture, meaning it cannot be seen in any form, but the Nemui Nyimah culture is always present in every activity or event such as deliberations, mulei menganai forums, yasinan, ngakuk majeu Nemui nyimah It is a concept. harmony between the differences in the lives of indigenous communities in Lampung.